STUDI TENTANG KINERJA PANITIA PEMBINA KESELAMATAN DAN KESEHATAN KERJA DI PT. PLN (PERSERO) AREA PELAYANAN DAN JARINGAN KUDUS - Hagianto Adiatma; Susi Sulandari; Nina Widowati (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
Study about performance the committee of the occupational safety and health (P2K3) effected by human resources that are within the occupational safety and health (K3) have a double job, any members who are in majority of P2K3 is not an expert in the field of K3. Lack of motivation of employees, and lack of motivation which is given by leader to the employee. This research was conducted using qualitative research methods are purely descriptive. Focus of research location on the PT. PLN (Persero) APJ Kudus. Selection of informants is done using a purposive sampling. To test the quality of the data used the technique of triangulation. Phenomena that affect organizational performance is measured through the dimensions of organizational performance according to Sudarmanto (2009: 13) by looking at the dimensions of productivity, quality, timeliness, resources management, and cost. As for looking at factors that affect organizational performance using the theory of Keith Davis of Mangkunegara (2006: 13) as seen from the factor of ability and motivation factors. Performance of the committee of occupational safety and health (P2K3) has not been optimal which is viewed of the dimensions of productivity, the quality, punctuality, the management of resources, and charges.The factors that influences the performance of an organization that is the lack of the ability of human resources in the field of occupational safety and health, and lack of motivation given by leader. Recommendations given that is, ( 1 ) held socialization about the importance of K3 in a company so employees aprovident about the importance of occupational safety and health; ( 2 ) providing education and training to an employee about occupational safety and health ; ( 3 ) the committee of occupational safety and health (P2K3) supposed to be filled by people who are completely proficient in the occupational safety and health ; and ( 4 ) the maintenance and observation and equipment to work safety and health.